SÍNDROME NEFRÓTICA EM MULHER JOVEM - NEM TUDO É LUPUS! - - Isabel Carolina Veríssimo Vendramini; Danielle Pereira Barros; Úrsula Soares Barbosa; Vanessa de Oliveira Magalhães; Nilzio Antônio da Silva; Jozelia Rêgo (UniEVANGÉLICA, 2017)
Objective: To present a case of nephrotic syndrome, secondary to syphilis, mimicking systemic lupus erythematosus. Case report: 26-year-old woman who developed painful oral ulcers, arthralgia and nephrotic syndrome, and the possibility of autoimmune disease was initially suggested. The results of the laboratory tests removed the possibility of systemic lupus erythematosus and confirmed the diagnosis of syphilis. Final considerations: The presence of nephrotic syndrome in a young female patient should trigger the investigation of previous sexual history, and syphilis is a mandatory possibility in this investigation, which can mimic SLE, delaying early diagnosis and effective treatment